ASSESSING PERSONAL INJURY LAWYERS ALLEGED MISAPPROPRIATION OF CLIENT COMPENSATION FUNDS IN SOUTH AFRICA: TAKING THE BRIEFS OUT OF THE BRIEFCASE - Masumbe, Paul S.; Thukuse, Bulelani; Phindelo, Usenathi (International Journal of Law in Changing World, 2025)
The Road Accident Fund (RAF) was created to provide social protection and compensation for victims of motor-vehicle accidents. Yet, its functioning has increasingly been compromised by unethical conduct from some legal practitioners. This paper examines the extent to which the RAF fulfills its mandate and the ways in which certain lawyers have misappropriated or withheld client compensation funds, violating fiduciary duties and constitutional rights. Through doctrinal research, it analyzes the legal framework governing RAF litigation, including the Road Accident Fund Act, the Legal Practice Act, Legal Practice Council Rules, and relevant constitutional provisions. Key case law is reviewed to illustrate judicial responses to professional misconduct. The findings indicate significant weaknesses in regulatory enforcement and oversight. The study concludes by proposing reforms to strengthen accountability, enhance claimant protection, and restore confidence in the legal profession’s role in RAF matters. __________ EVALUACIÓN DE LA ALEGACIÓN DE APROPIACIÓN INDEBIDA DE FONDOS DE COMPENSACIÓN DE CLIENTES POR ABOGADOS DE LESIONES PERSONALES EN SUDÁFRICA: RETIRANDO LOS ARCHIVOS DEL MALETÍN El Fondo de Accidentes de Tránsito (RAF) se creó para brindar protección social e indemnización a las víctimas de accidentes automovilísticos. Sin embargo, su funcionamiento se ha visto cada vez más comprometido por la conducta poco ética de algunos profesionales del derecho. Este documento examina hasta qué punto el RAF cumple con su mandato y las formas en que ciertos abogados han malversado o retenido fondos de compensación de clientes, violando deberes fiduciarios y derechos constitucionales. A través de una investigación doctrinal, se analiza el marco legal que rige los litigios del RAF, incluyendo la Ley del Fondo de Accidentes de Tránsito, la Ley de Práctica Legal, el Reglamento del Consejo de Práctica Legal y las disposiciones constitucionales pertinentes. Se revisa la jurisprudencia clave para ilustrar las respuestas judiciales a la mala conducta profesional. Los hallazgos indican deficiencias significativas en la aplicación y supervisión regulatoria. El estudio concluye proponiendo reformas para fortalecer la rendición de cuentas, mejorar la protección de los demandantes y restablecer la confianza en el papel de la abogacía en asuntos relacionados con el RAF. __________ 评估南非人身伤害律师涉嫌挪用客户赔偿金的行为：揭开法律的神秘面纱 道路交通事故基金（RAF）的设立旨在为机动车事故受害者提供社会保障和赔偿。然而，一些法律从业人员的不道德行为日益损害了该基金的运作。本文探讨了道路交通事故基金履行其职责的程度，以及某些律师挪用或扣留客户赔偿金、违反信托义务和宪法权利的方式。通过法理学研究，本文分析了道路交通事故基金诉讼的法律框架，包括《道路交通事故基金法》、《法律执业法》、《法律执业委员会规则》和相关宪法条款。本文还回顾了关键案例，以说明司法机关对职业不当行为的回应。研究结果表明，监管执法和监督方面存在重大缺陷。该研究最后提出改革建议，旨在加强问责制、提升索赔人保护，并恢复公众对法律界在道路交通事故基金（RAF）事务中所扮演角色的信心。